Creating equitable spaces for all learners: leveraging community expertise through situationally responsive instructional conversations - Holmes, Melissa A. (Kansas State University, 2022)
This qualitative study utilized positive discourse analysis (PDA) to explore the classroom discourse practices of three grade-level teachers at a highly diverse school. The purpose of the study was to investigate ways elementary teachers who employ biography-driven instruction (BDI) (e.g., Herrera, 2016) use discourse to invite and nurture student willingness to share about and maximize the sociocultural and linguistic dimensions of their biographies. The research questions guided investigation of (1) formal text properties of instructional conversation (ICs), (2) ways the social practices of the classroom influenced the discourse, and (3) institutional factors that challenged and supported use of culturally responsive/sustaining discourse practices. Two primary sources of data included video of classroom instruction and two-part individual interviews. The interviews included video elicitation, which supported analysis of IC texts created from eleven selected episodes of IC. They also incorporated use of a semi-structured interview protocol to support exploration of institutional factors that influenced the three participants’ use of culturally responsive/sustaining discourse. Additional sources of data (e.g., documents, questionnaire, analytic memos) provided context regarding the members of the classroom learning communities and supported data analysis. This study employed Fairclough’s (1989) three-part analysis progression of description (exploring aspects of the text itself), interpretation (focusing on the relationship between the situational context and the text), and explanation (making connections to broader institutional and societal contexts). Findings and conclusions revealed that culturally responsive/sustaining discourse (a) fostered relationships among members of the classroom community, (b) positioned students as knowledgeable and capable, (c) created a risk-free space for sharing knowledge and ideas, and (d) fostered equitable participation of all students. Social practices of the classroom influenced the discourse in multiple ways and indicated that (a) use of mediation tools scaffolded engagement and language use, (b) use of multiple grouping structures fostered student talk, and (c) situationally attending to what students produced created opportunities to elicit and leverage assets. Building-level leadership was the most influential factor on the teachers’ use of culturally responsive/sustaining discourse. The explanation phase of analysis (Fairclough, 1989) also included exploration of social determinants that influenced the discourse as well as the effects of the discourse in relation to ongoing struggles at situational, institutional, and societal levels. Many of the social determinants reflected hegemonic influences (e.g., cultural, linguistic) and deficit perspectives. Others were related to typical interaction patters found in U.S. classrooms. Transformative influences of the IC discourse often revealed aspects of an asset perspective on culturally and linguistically students and emphasized pluralism (e.g., linguistic, epistemological). The teachers’ ICs illustrated how educators can create educational spaces that foster students’ sense of belonging and positive self-concept. The episodes further highlighted ways teachers can collaborate with students to leverage the expertise of all members of the classroom community toward collective learning and success. Processes that ensured equitable participation among all members of the community also were identified as transformative influences.
Keywords: Pedagogy; English as a second language; Elementary education; Culturally responsive/sustaining; Biography-driven instruction; Positive discourse analysis